2008
DOI: 10.1111/j.1751-9004.2008.00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the Links between Narcissism and Self‐esteem: A Theoretical and Empirical Review

Abstract: The links among narcissism, explicit (deliberate, controllable) self‐esteem, and implicit (automatic, uncontrollable) self‐esteem are unclear despite numerous attempts to illuminate these links. Some investigations suggest that narcissism reflects high explicit self‐esteem that masks low implicit self‐esteem, but other investigations fail to replicate this pattern. Here, we place the ‘mask’ model of narcissism in historical context and review the existing empirical evidence for this model. We then discuss thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
220
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(238 citation statements)
references
References 78 publications
13
220
2
3
Order By: Relevance
“…Some such research exists, although it has largely focused on self-esteem instability [48][49] or focused solely on grandiosity [50].…”
Section: Moving Forward: Studying Dynamic Within-person Processesmentioning
confidence: 99%
“…Some such research exists, although it has largely focused on self-esteem instability [48][49] or focused solely on grandiosity [50].…”
Section: Moving Forward: Studying Dynamic Within-person Processesmentioning
confidence: 99%
“…One direct prediction based on psychodynamic theory concerns narcissism. The mask model of narcissism assumes that narcissistic individuals are characterized by deep self-doubt (corresponding to low implicit self-esteem), which they compensate for by projecting grandiose self-views (corresponding to extremely high explicit self-esteem) (Bosson et al, 2008 ). Empirical evidence supporting this model has remained mixed, however, perhaps partly because of the relative unreliability of measures of implicit self-esteem (Bosson et al, 2000 ).…”
Section: Improving Implicit Self-esteemmentioning
confidence: 99%
“…On the other hand, observed correlations are sometimes unexpectedly small. For example, various studies have found that the correlation between name letter preferences and narcissism ranges from r = -.08 to r = 0.17 (Bosson et al, 2008), possibly due to psychometric or other defects in the measurement of the former (Hoorens, 2014). Consequently, our expectations here were tentative.…”
Section: Methodsmentioning
confidence: 61%